Serum Tenascin-C as a Novel Predictor for Risk of Coronary Artery Lesion and Resistance to Intravenous Immunoglobulin in Kawasaki Disease – A Multicenter Retrospective Study - Yoshida, Toshimichi; Imanaka-Yoshida, Kyoko; Abe, Jun; Ichida, Fukiko; Suda, Kenji; Nakaoka, Hideyuki; Yoshikane, Yukako; Matsushita, Takeji; Okuma, Yoshiaki; Shiraishi, Isao; Hiroe, Michiaki; Katsube, Yasuhiro; et al. (Circulation Journal, 2016)
Background:Tenascin-C (TN-C) is an extracellular matrix glycoprotein that is heavily upregulated at sites of inflammation. We conducted a retrospective study to assess the utility of TN-C as a novel biomarker to predict the risk of developing coronary artery lesions (CAL) and resistance to intravenous immunoglobulin (IVIG) in patients with Kawasaki disease (KD).Methods and Results:We collected blood samples of 111 KD patients (IVIG-responder: 89, IVIG-resistant: 22; CAL: 8) and 23 healthy controls, and measured the serum levels of TN-C. TN-C levels on admission were significantly higher in patients than in healthy controls and in patients during convalescence after IVIG administration (69.6 vs. 20.4 vs. 39.7 ng/ml, respectively; P<0.001), and correlated positively with C-reactive protein (P<0.001), neutrophil (percentage; P=0.005), and ALT (P<0.001), and negatively with platelet count (P=0.023) and sodium level (P=0.025). On admission, TN-C levels in patients who later developed CAL were significantly higher than in those without CAL (P=0.010), and significantly higher in IVIG-resistant subjects than in IVIG-responders (P=0.003). The accuracy of TN-C testing for the prediction of IVIG resistance was comparable to that of the Kobayashi score.Conclusions:Serum TN-C could be a biomarker for predicting the risk of developing CAL and IVIG resistance during the acute phase of KD. (Circ J 2016; 80: 2376–2381)